The Effect of Picture Series Model, Gender, and Learning Mode on Students' Writing Achievement - Haderaerani Haderaerani; Alberth Alberth; La Ode Nggawu (Journal of Language Education and Educational Technology (JLEET), 2024)
This study examines the effect of picture series, a visual media consisting of sequential images, on the writing achievement of VIII graders at SMPN 2 Sampara, considering gender and learning mode (WhatsApp vs. Conventional). The research aims to determine if there is a difference in writing outcomes between students using picture series through WhatsApp and those using conventional methods, and to explore the interaction between picture series models and gender. The population consisted of 57 students, divided into a WhatsApp class (28 students) and a conventional class (29 students). Using a quasi-experimental design, the WhatsApp class (VIII2) served as the experimental group, while the conventional class (VIII3) was the control group. Data were collected through pre-test and post-test scores. Findings indicate a significant difference in writing outcomes, with the WhatsApp class outperforming the conventional class. A two-way ANOVA revealed an interaction between picture series models and gender, with a significance value of 0.000 < 0.05, indicating a notable interaction. The Estimated Marginal Means graph showed intersecting lines, further supporting this interaction. Additionally, no significant difference was found in writing outcomes for male students between the two methods. However, female students using the WhatsApp method achieved higher scores than their male counterparts.